Assessment of COVID-19 pandemic stress among health sciences students in a private university in South-West Nigeria (Journal of Ideas in Health, 2021)
Background: COVID-19 pandemic has been reported to have psychological effects on various aspects of human life and segments of society. The study aimed to assess COVID-19 pandemic stress during and after lockdown among health sciences students at a private university in South-West, Nigeria.Method: A descriptive, cross-sectional web-based research was conducted in a private teaching hospital of a private university using a simple random sampling technique. The study instrument was a self-structured questionnaire containing sociodemographic details and questions adapted from the validated Perceived Stress Scale (PSS) by Sheldon Cohen regarding lectures during and after COVID-19 lockdown. Data were analyzed with the aid of SPSS version 26 software.Results: A total of 220 respondents were included in the study, with a mean age of 22.08±2.996. Most of the respondents were females (157, 71.4%) in their 4th-year level (37%). The participants had a high level of stress during (46.8%) COVID-19 lockdown than after the lockdown (29.1%), and statistical significance was observed between the perceived stress level during and after the COVID-19 lockdown (McNemar-Bowker’s value = 29.322, P =
Keywords: COVID-19 Pandemic, Online Classes, Perceived Stress Level, Private University, Health Sciences Students, Lockdown, Nigeria